The Teaching of Elder Joseph the Hesychast on Man’s Ascent to Theosis as Presented in His Work «The Ten-Voiced Spirit-Moving Trumpet» - Hieromonk Pavel (Egor O. Polevoy); Priest Andrei E. Lysevich (Вестник Екатеринбургской духовной семинарии, 2025)
The present paper attempts to investigate for the first time the main written work of St. Joseph (Kottis) the Hesychast known as The Ten-Voiced Spirit-Moving Trumpet, from a scientific perspective. The legacy of the elder consists mainly of letters and poems. His life and teachings are described with varying degree of detail in the works of his disciples, Archimandrite Ephraim of Philoteou (Arizona) and monk Joseph of Vatopedi. The only existing complete commentary on The Decaphonic Trumpet has been written by monk Joseph, but it reflects rather his personal understanding of the elder’s teachings and has no systematic scholarly nature. There is also a monograph published in 2017 by priest Christian Groza and entitled «The Elder Joseph Hesychast. Life and Teachings»: it provides analysis of the ‘Epistle to the Desert Hesychast’, while making no mention of The Decaphonic Trumpet which in fact completes and complements the «Epistle…». Thus, the main work of the elder still remains essentially unexplored. An attempt to fill this gap is made in this article, the purpose of which is to investigate the teaching of man’s ascent to theosis as presented by St. Joseph in The Decaphonic Trumpet in the context of patristic tradition. The bibliography of existing commentaries and studies of the source is examined. The genre, style, content and other characteristics of the analyzed work of St. Joseph are considered in the context of patristic teaching, especially in comparison with the «The Ladder» by St. John Climacus. It is concluded that there are elements of uniqueness and novelty in the elder’s description of the process of ascent to theosis, and in the degree of his detailing certain spiritual stages, as well as in the terminology he used. At the same time, it is stated that the teachings of Venerable Joseph the Hesychast are fully consistent with the patristic tradition, he is a faithful follower and successor of the ascetic and theological tradition of St. Paul, St. Dionysius the Areopagite, St. Isaac the Syrian and the holy fathers of later times, up to the Athonite ascetics of the 20th century.